2019
DOI: 10.1186/s12962-019-0191-6
|View full text |Cite
|
Sign up to set email alerts
|

Cost-comparison analysis of a multiplatform tumour profiling service to guide advanced cancer treatment

Abstract: Background Tumor profiling is increasingly used in advanced cancer patients to define treatment options, especially in refractory cases where no standard treatment is available. Caris Molecular Intelligence (CMI) is a multiplatform tumor profiling service that is comprehensive of next-generation sequencing (NGS) of DNA and RNA, immunohistochemistry (IHC) and in situ hybridisation (FISH). The aim of this study is to compare costs of CMI-guided treatment with prior or planned treatment options in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Overall, our study provides a real-world experience of the impact of CGP in a community-based academic NCI-designated cancer center serving a highly diverse patient population, where molecular testing is based on a two-tier testing algorithm. While recognizing that a 10% overall rate of management change that is based on CGP is very modest, its use in certain subsets, such as advanced NSCLC, where the impact currently is most significant appears to be justifiable and it has been found to be cost effective [40][41][42]. In addition, we have identified multiple reasons for the relatively smaller clinical impact of CGP in other tumor types, despite a much larger proportion of patients with actionable genomic alterations reported.…”
Section: Discussionmentioning
confidence: 91%
“…Overall, our study provides a real-world experience of the impact of CGP in a community-based academic NCI-designated cancer center serving a highly diverse patient population, where molecular testing is based on a two-tier testing algorithm. While recognizing that a 10% overall rate of management change that is based on CGP is very modest, its use in certain subsets, such as advanced NSCLC, where the impact currently is most significant appears to be justifiable and it has been found to be cost effective [40][41][42]. In addition, we have identified multiple reasons for the relatively smaller clinical impact of CGP in other tumor types, despite a much larger proportion of patients with actionable genomic alterations reported.…”
Section: Discussionmentioning
confidence: 91%
“…However, while the clinical utility of single biomarkers, such as KRAS [205] and MSI-H/dMMR [10], have been proved to extend survival of CRC patients, the role of comprehensive molecular profiling remains largely questionable. Moreover, only a limited number of studies have investigated the cost-effectiveness of molecular profiling in cancer patients [206][207][208][209][210]. For instance, a study conducted in NSCLC patients showed that NGSbased parallel testing was more cost-effective than single-gene-based testing [207].…”
Section: Challenges In Biomarker Research and Future Perspectivementioning
confidence: 99%
“…Other commercial NGS panel tests interrogate both at the DNA and RNA level, like Caris. 45 Some NGS platforms combine DNA-based and RNA-based NGS panels in the same tissue sample, like the Oncomine Focus Assay 15 (ThermoFisher) as tested in the tepotinib VISION trial. Real-time PCR assays using RNA from tissue samples are currently in development; however, they have not yet been accepted or qualified to become companion diagnostic assays.…”
Section: Molecular Diagnosis Of Met Exon 14 Skipping Alterationsmentioning
confidence: 99%